'Regime vetting': a technique to exercise EU market power. Issue 4 (3rd April 2022) - Jarlebring, Johannes
ABSTRACT: There is a broad consensus that the EU has great sources of power but little agreement on how and when this power is actively leveraged to shape global market regulation. Scholars have noted a widespread fragmentation and called for studies that cover multiple cases and account for how contextual factors influence strategic aims. This article responds to these calls by conceptualizing 'regime vetting' as a technique used by the European Union to reach beyond its borders in various sectors. By coining this term, the article enables exploration of a form of active and de-centred power projection that leverages the EU's main sources of power. The article also offers a typology of four different types of regime vetting and propositions on how internal and external contextual factors systematically shape the strategic uses of regime vetting, thereby contributing to the theoretical discussion on how 'context matters' in shaping EU external action.